(W1‐x, Mx)C carbides with desired combinations of compatible density and properties – A first‐principles study. Issue 8 (28th April 2021) - Liu, Ruiliang; Zhang, Dong; Tang, Yunqing; Tang, Xinhu; Humphries, Edward; Li, Dongyang
Abstract: Tungsten monocarbide (WC) is one of the highly valuable hard materials for industry, widely used as reinforcement in hardfacing overlays, thermal spray coatings, composites, and various alloys. However, its large density leads to the inhomogeneous distribution of WC particles in the metal‐matrix hardfacing overlays. It is highly wished to have appropriate reinforcing phases with an optimal combination of high strength, compatible density, and physical properties. In this study, we tailored WC by partially substituting W with 3d and 4d transition metals through first‐principles calculations. It is demonstrated that WC can be tailored by element‐substitution with desired properties. Identified stable ( W 1 ‐ x, M x ) C carbides possess lowered density and mechanical properties that are comparable to those of WC. Physical properties, for example, the Debye temperature, Grüneisen parameter, and thermal conductivity, of the tailored carbides are also studied for widened applications. Efforts are made to generate comprehensive information on metal‐substituted ( W 1 ‐ x, M x ) C with elucidated underlying mechanisms through analyzing the corresponding electronic characteristics.